Fathers' and Mothers' Emotional Accessibility and Youth's Developmental Outcomes. Issue 2 (15th March 2017) - Clay, David; Coates, Erica; Tran, Quynh; Phares, Vicky
ABSTRACT: This study examined the association between parents' emotional accessibility and youth's functioning. Participants included 154 parents who completed measures of parental emotional accessibility and their children's emotional and behavioral problems. Results showed that mothers are more emotionally accessible to their children. Mothers' emotional accessibility was associated negatively with youth's emotional and behavioral problems; whereas, fathers' emotional accessibility was associated with only youth's behavioral problems. This study highlights the importance of examining parental emotional accessibility when studying youth's development, utilizing parental perceptions to learn about youth and family functioning, and actively including fathers in family research studies.